Verbal Intelligence: A Key of Students Development - Dewi, Anggita Tiara; Subiyantoro, Slamet; Sarwanto, Sarwanto (Universitas Pendidikan Ganesha, 2022)
Students in elementary schools often experience various developmental disorders, especially those related to verbal intelligence, so that students experience difficulties in acquiring basic skills such as writing, reading, or speaking. Therefore, it is necessary to analyze to measure the verbal intelligence ability of students from an early age when in elementary school. This study aims to explore the verbal intelligence of students in the overall aspects, namely: reading, writing, listening, and speaking. This research uses descriptive qualitative research with a case study model. In collecting data, the researcher used a tool, namely audio-based stories, then strengthened interviews (unstructured) with educators and students with 25 respondents. Analysis of the data using Miles and Huberman. The study’s overall students' verbal intelligence still must be considered. In general, it is proven that almost half of students still lack in listening, reading, writing, and speaking aspects, so this will certainly hinder the development of students at their age. The implication of this research is the need for support from relevant stakeholders to develop verbal skills from an early age so that it becomes the key to the development of students in the future.